Genotoxicity testing of chromium trioxide - a study using Vicia bioassay - Mishra, S N; Abha, Abha; Jha, Anand M (Journal of Phytology, 2012)
In the present study by employing highly sensitive and simple plant bioassay, Vicia faba cytogenetic test, genotoxic property of chromium trioxide (CrO3) was evaluated. Roots of Vicia faba were treated with 10, 20. 30, 40 and 50 mg/l of CrO3 at room temperature in dark. The dosages selected for evaluation were below LD50 dose of the compound. Cytotoxicity and chromotoxicity were expressed in terms of depression in mitotic activity and frequency of chromosomal aberrations in mitotic phases. Treatment of roots caused dose and period of treatment related inhibition of mitotic activity. Dose related increase in the frequencies of cells with chromosomal aberration in metaphase and anaphase stages were observed. Statistical analysis revealed significant effects of dose and periods of treatment. The results indicate genotoxic potential of chromium trioxide in the dose range tested.